2022
DOI: 10.5650/jos.ess21115
|View full text |Cite
|
Sign up to set email alerts
|

Baru (<i>Dipteryx alata</i> Vogel) Oil Extraction by Supercritical-CO<sub>2</sub>: Improved Composition by Using Water as Cosolvent

Abstract: be affected by the methods used for oil extraction. Minor components in plant oils contain antioxidants that impact on oil stability and on consumers health, such as phytosterols that may help control consumers cholesterol levels in blood, and volatile and partially volatile compounds that impact on oil flavor, among other minor components that impact on oil value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Regarding tocopherol contents, we have found 28.9 mg/kg of tocopherols in Baru oil, In fact, the tocopherol content is low when compared to other almond oils, such as Fournat, Ferraduel, and Ferragnes [ 25 ]. Although it is not possible to state the reason for this difference, a recent study demonstrated that the conditions of Baru oil extraction could interfere with tocopherol contents [ 26 ]. Despite this, it is reasonable to highlight other nutritional qualities of the Baru oil, notably rich in oleic, linoleic, and linolenic fatty acids and poor in saturated fatty acid palmitate [ 1 , 2 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tocopherol contents, we have found 28.9 mg/kg of tocopherols in Baru oil, In fact, the tocopherol content is low when compared to other almond oils, such as Fournat, Ferraduel, and Ferragnes [ 25 ]. Although it is not possible to state the reason for this difference, a recent study demonstrated that the conditions of Baru oil extraction could interfere with tocopherol contents [ 26 ]. Despite this, it is reasonable to highlight other nutritional qualities of the Baru oil, notably rich in oleic, linoleic, and linolenic fatty acids and poor in saturated fatty acid palmitate [ 1 , 2 , 27 ].…”
Section: Discussionmentioning
confidence: 99%